Structural requirements for the interaction of 5S rRNA with the eukaryotic transcription factor IIIA. - Pieler, T (1984)
In order to study the binding of the eukaryotic transcription factor IIIA to heterologous 5S rRNAs with a low degree of overall sequence conservation (less than 20%) we have utilized a transcription competition assay involving eubacterial, archaebacterial and eukaryotic 5S rRNAs. All the molecules inhibit Xenopus 5S rRNA transcription specifically, which suggests that only a small amount of specific conserved RNA sequences, if indeed any, are essential for the interaction of the transcription factor with the 5S rRNA molecule, whereas universal 5S rRNA secondary structure elements seem to be required. A fragment of Xenopus laevis oocyte 5S rRNA (nucleotides 41-120), which partially maintains the original 5S rRNA structure, also competes for TF III A. In vitro transcription of a naturally occurring mutant of the Xenopus laevis oocyte 5S rRNA gene, the pseudogene, which carries several point mutations within the TF III A binding domain is equally inhibited by exogenous Xenopus 5S rRNA.